History and heritage of mathematical sciences (Sukṛtīndra Oriental Research Institute, 2009)
Contributed papers presented at an International Conference on the History and Heritage of Mathematical Sciences and Role of Technical Literature in Sanskrit and Other Languages held during the Annual Conference of Indian Society for History of Mathematics at the Sukṛtīndra Oriental Research Institute in Dec. 2002.